STUDY ON THE CONFORMATIONS OF p-(NITRO)METHOXYCALIX[4]ARENE AND p-(tert-BUTYL)METHOXYCALIX[4]ARENE USING. HIGH LEVEL AS INITIO METHOD - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT Ab initio calculations have been performed in order to investigate the conformational characteristics of p- (nitro)methoxycalix[4]arene and p-(terl-butyl)methoxycalix[4]arene. The structures of four types (cone, parlial cone, 1,2-altemate and 1,3-altemate) of conformers for each compound have been optimized byab initio method at the restricted Meller-Plesset fourlh-order perlurbatlon (RMP4) level of theory using 6-311G and 6-311G++(d,p) basis sets. General trends in relative stabilities of p-(nitro)methoxycalix[4]arene and p-(terl-butyl)methoxycalix[4]arene are similar and decrease in following order: parlial cone> cone> 1,3-altemate > 1,2-altemate. The calculated results of the most stable conformation of parlial cone structure agree with.the reporled NMR experimental observations.